IMPLEMENTASI MOTIVASI KERJA TERHADAP KINERJA KARYAWAN KYO SERVICED APARTMENT JAKARTA SELATAN - Dewi Sartika; M. Anton Nurhidayat (Jurnal Ekonomi dan Manajemen, 2025)
This study aims to analyze the employee recruitment process at Kyo Serviced Apartment, particularly in terms of the relationship between motivation, feedback, and employee performance. A descriptive qualitative approach was employed to illustrate the internal dynamics, using data collection techniques through observation and in-depth interviews with employees. The results indicate a significant relationship between praise, motivation, and improved employee performance. A lack of appreciation and constructive feedback tends to cause dissatisfaction, which may impact productivity. Through a SWOT analysis, it was found that the company’s main strength lies in harmonious working relationships, while its weakness lies in the lack of recognition for individual contributions. This study recommends the implementation of more personalized motivation, as well as a combination of intrinsic and extrinsic motivational approaches to create a more productive and harmonious work environment. These findings are expected to serve as an evaluation and improvement material for human resource policies within the company.